Cytotoxic prenylated xanthone and coumarin derivatives from Malaysian Mesua beccariana - Karunakaran, Thiruventhan; Ee, Gwendoline C.L.; Tee, Keng H.; Ismail, Intan S.; Zamakshshari, Nor H.; Peter, Waziri M. (Elsevier Ltd, 2016)
Our recent research on the phytochemical constituents of the stem bark of Mesua beccariana gave one new xanthone, beccarixanthone T (1) and one new coumarin, beccamarin T (2) together with three known xanthones mesuarianone (3), mesuasinone (4), 1,5-dihydroxyxanthone (5) and four known terpenoids, friedelin (6), stigmasterol (7), beta-sitosterol (8) and gamma-sitosterol (9). The structures of these compounds were elucidated and determined using spectroscopic techniques such as NMR and MS. The cytotoxic activities of compounds 1-4 as well as the crude extracts were tested againsttwo cancer cell lines, Hep G2 (liver cancer cell line) and HT-29 (colon cancer cell line) using MTTassays. Mesuarianone (3) gave a significant activity on the HT-29 cell line while mesuasinone (4) gave moderate activity against HT29 cell line